2020
DOI: 10.1021/acscombsci.0c00027
|View full text |Cite
|
Sign up to set email alerts
|

TRAF2 and NCK-Interacting Kinase Inhibitors for Colorectal Cancer: In Vitro and Theoretical Validations

Abstract: TRAF2 and NCK-interacting kinase (TNIK) is a critical factor in colorectal cancer (CRC) proliferation mediated by Wnt signaling. We attempted to identify efficient TNIK inhibitors using computational high-throughput virtual screening (HTVS) from various drug banks and databases. By performing/on performing e-pharmacophore screening and molecular docking methods, from ∼700 000 molecules, compounds LC_222150, LC_112060, and LC_64796 were identified as potential leads, through molecular dynamics (MD) simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 7 , 11 , 12 In addition, KEGG pathway enrichment indicated that TNIK-related proteins were also involved in cancer pathways, which is well verified in previous data. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 GeneMANIA is an online analysis tool for deriving hypotheses based on gene functions. 40 GeneMANIA is a flexible user-friendly website for PPI network construction based on genomic, proteomic, and gene function data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 11 , 12 In addition, KEGG pathway enrichment indicated that TNIK-related proteins were also involved in cancer pathways, which is well verified in previous data. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 GeneMANIA is an online analysis tool for deriving hypotheses based on gene functions. 40 GeneMANIA is a flexible user-friendly website for PPI network construction based on genomic, proteomic, and gene function data.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The use of a synthesized TNIK-inhibiting peptide down-regulates cell-surface GRIA1 levels and AMPAR-mediated currents in rat hippocampal cultures. 9 Moreover, using genetic and bioinformatic methods, many recent reports have proposed TNIK as an anticancer target molecule 17 in many types of cancers, such as colorectal cancer, 18 , 19 , 20 hepatocellular carcinoma, 21 lung cancer, 22 synovial sarcoma, 23 prostate cancer, 24 and breast cancer. 25 TNIK has been shown to have potential importance in schizophrenia, 9 , 26 , 27 , 28 attention-deficit/hyperactivity disorder (ADHD), 29 and bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%